Convalescent plasma or hyperimmune immunoglobulin for people with COVID‐19: a living systematic review - Piechotta, V; Iannizzi, C; Chai, KL; Valk, SJ; Kimber, C; Dorando, E; Monsef, I; Wood, EM; Lamikanra, AA; Roberts, DJ; McQuilten, Z; So-Osman, C; et al. (Cochrane Collaboration, 2021)
Background Convalescent plasma and hyperimmune immunoglobulin may reduce mortality in patients with viral respiratory diseases, and are being investigated as potential therapies for coronavirus disease 2019 (COVID‐19). A thorough understanding of the current body of evidence regarding benefits and risks of these interventions is required.